Seismic Behavior of Innovative Precast Superimposed Concrete Shear Walls with Spiral Hoop and Bolted Steel Connections - Xi Wu; Meng-fu Wang; Ze-long Liu (Advances in Civil Engineering)
Owing to the desirable bond strength and excellent workability, spiral hoop and bolted steel connectors are introduced to enhance the connecting performance of superimposed reinforced concrete shear wall (SRCSW) system. In order to investigate the seismic performance of SRCSWs, applying such connecting methods under flexure-shear interaction and flexural dominated status, two groups of precast (PC) specimens were constructed: one-story and two-story specimens. Seismic behavior in terms of crack patterns, load-displacement response, ductility, stiffness degradation, strain response, and deformation results of SRCSWs is evaluated by the quasistatic cyclic test. It is shown that the wall specimens with the proposed connectors exhibited similar failure mode to that of the cast-in-place (CIP) walls and possessed adequate seismic performance such as lateral resistance, ultimate drift ratio, and lateral stiffness besides the ease of erection. The strain responses and deformation results of the PC specimens under reversed cyclic loading were presented to evaluate the effectiveness of the introduced connections. The test results indicated that the PC walls adopting bolted steel connectors behaved better in force transmission and exhibited greater integrity characteristic compared with the specimens having spiral hoop connectors. Lastly, simplified finite element models considering the nonlinear slip behavior within the connection joint of SRCSWs were established and verified, which could provide sufficient accuracy and efficiency to predict the seismic response of the proposed wall system.